HASIL BELAJAR KOGNITIF IPA FISIKA SISWA MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING CHIPS di KELAS VIII MTs DAARUN NAHDHAH TAWALIB BANGKINANG KAMPAR - Hidayatullah, Futri; Islami, Nur; Irianti, Mitri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research aims to describe and differentiate the cognitive learning result physics science between the implementation of cooperative learning type talking chips group with conventional learning group. This type of research is a quasi-experimental, with a intact group comparison design. Population in this research is all of VIII classes with 198 students. Meanwhile the samples are 29 students in VIII A as control class and 29 students in VIII B as experiment class. The instrument of data in this research is a score cognitive performance test which consists of 20 multiple choice items. Analysis of the data in this study was a descriptive analysis that was used to determine the performance of the physics cognitive learning through the criteria of absorption and effectiveness of learning. The inferential analysis was used to differentiate a cognitive learning considerably using independent samples t-test. The analysis data shows: the average absorption of the experiment class is 80% of the higher in category, and declared effective learning efficiently. Meanwhile the average absorption of the control class 74.83%. Therefore, it can be concluded that implementation of cooperative learning type talking chips can be used as an alternative in the learning process in the classroom VIII MTs Daarun Nahdhah Tawalib Bangkinang Kampar.Keywords: Cognitive result test, optical instruments, talking chips.